Oxidative nucleophilic substitution selectively produces cambinol derivatives with antiproliferative activity on bladder cancer cell lines. Issue 1 (1st January 2019) - Botta, Lorenzo; Filippi, Silvia; Bizzarri, Bruno Mattia; Meschini, Roberta; Caputo, Manuela; Proietti-De-Santis, Luca; Iside, Concetta; Nebbioso, Angela; Gualandi, Giampiero; Saladino, Raffaele
Graphical abstract: Highlights: Methyltrioxorhenium catalyzes a versatile and selective late stage oxidative nucleophilic substitution reaction. Oxidative nucleophilic substitution yielded cambinol derivatives with anti-proliferative activity. The lead compound of the series neither inhibits SIRT 1 enzyme nor influences p53 protein. Abstract: Methyltrioxorhenium mediated oxidative addition/elimination nucleophilic substitution yielded alkylamino and arylamino cambinol derivatives characterized by anti-proliferative activity against wild-type and p53 mutated MGH-U1 and RT112 bladder cancer cell lines. Some of the novel compounds showed an activity higher than that of the lead compound. The reaction was highly regioselective, affording for the first time a panel of C-2 cambinol substitution products. Aliphatic primary and secondary amines, and primary aromatic amines, were used as nitrogen centered nucleophiles. Surprisingly, the antiproliferative activity of C-2 substituted cambinol derivatives was not correlated to the induction of p53 protein, as evaluated by the analysis of the cell viability on wild-type and p53 mutated cancer cell lines, and further confirmed by western blot analyses. These data suggest that they exert their antiproliferative activity by a mechanism completely different from cambinol.